Distribution and Habitat Preferences of the Newly RediscoveredTelmatogeton magellanicus(Jacobs, 1900) (Diptera: Chironomidae) on Navarino Island, Chile - Lorenz Simoes, Felipe; Contador Mejias, Tamara Andrea; Rendoll-Carcamo, Javier; Perez-Troncoso, Carolina; Hayward, Scott A. L.; Turner, Edgar; Convey, Peter (My University, 2020)
The habitat of the intertidal flightless midgeTelmatogeton magellanicus(Jacobs, 1900) is described for the first time from the northern coast of Navarino Island, Tierra del Fuego, Chile. Additionally, we report the first observations of adult behaviour in the wild. We delineate the species' distribution across three tidal zones (high, mid and low), and identify substrate characteristics that favour the presence of the midge. The mid-tide zone was the key habitat utilized byT. magellanicus, with lower densities in the low-tide zone and no presence in the high-tide zone. There was a strong association between the presence of larvae and filamentous algae, especiallyBostrychiaspp. and, to a lesser extent,Ulvaspp., as well as between larvae and the presence of larger, more stable boulders. As a result, the species' overall distribution was widespread but patchy. We suggest that the main limiting factor is the relative humidity experienced in different habitats. One of the most striking features of the behavioural observations during data collection was the extremely active adults, which suggests high energy expenditure over a very short period of time. This may be due to the limited time available to find mates in a single low-tide period, when adults have about three hours after emerging from the pupa to complete mating and oviposition before inundation by the tide. The data presented here provide a baseline for future studies on this species' ecology, phenology, physiology and general biology.
Keywords: algae; brachypterous; flightless; intertidal; life history; magellanic; non-biting midge; polar; sub-antarctic